Estudo do movimento migratório dos alunos brasileiros que cursam medicina em Cidade do Leste - Paraguai - Wrobel, Célia Gesica Belotto (2024)
This dissertation explores the migration of Brazilian students to Paraguay, focusing on medical students in Ciudad del Este. The study analyzes the economic and personal motivations that lead these students to choose Paraguay, including the lower cost of education and the easier admission process compared to Brazil. The research also investigates the challenges faced in the process of migration regularization, such as bureaucratic complexity, lack of clear information, and perceptions of corruption. Utilizing a comprehensive methodology that includes literature review, document analysis, consultations with journalistic sources, and semistructured interviews, the study provides a detailed view of the students' experiences. The results indicate that although many students attempt to regularize their status early in their stay, they encounter significant obstacles that complicate the process. Furthermore, the research highlights the socioeconomic diversity of the students, ranging from low to high family incomes, reflecting a broad spectrum of backgrounds. The dissertation also reveals that despite the difficulties, many students manage to adapt to the new environment, challenging initial negative perceptions about Paraguay. The study concludes with recommendations for more effective public policies aimed at facilitating the integration and regularization of students, promoting a more welcoming and secure educational environment. These measures are essential to improving the educational and migratory experience of Brazilian students in Paraguay.